If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5.7 + 1.6n = 1.38 Solving 5.7 + 1.6n = 1.38 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5.7' to each side of the equation. 5.7 + -5.7 + 1.6n = 1.38 + -5.7 Combine like terms: 5.7 + -5.7 = 0.0 0.0 + 1.6n = 1.38 + -5.7 1.6n = 1.38 + -5.7 Combine like terms: 1.38 + -5.7 = -4.32 1.6n = -4.32 Divide each side by '1.6'. n = -2.7 Simplifying n = -2.7
| 4-2x+7-3x+5=2x+4x-8+3x-x-3 | | 12+20x=5(4x+3) | | 7+77x=44x+19 | | -5(2t+5)=-35 | | 5+8z-4=5z+6-2z | | 5(f-4)=-40 | | log(5-t)+log(5+t)=1.2 | | 10(s-7)=-173 | | 21-(x+1)=5(x+5) | | -x/7=1/8 | | 6r+7=41r+14 | | x/9-7=-6 | | x=2/3(-3)+1 | | x^3=61 | | x=2/3(-3) | | 2(y+6)=2(y-3) | | 4y^3-10y^2= | | x=2/3(-6) | | 3m^2-9m-6m+30=2m^2-4m | | 3(4s+10)=138 | | 2/3*1269/1= | | 0.33(0.2x-1)+0.35x=0.05(3x+7) | | 2/3*1269= | | y^2+3x+10y+16=0 | | (3y-8)(2y+5)= | | 8a^2-5a-8=0 | | 3m(m-3)*-6(m-5)=2m^2-4m | | 2(2l+9)=38 | | 3m(m-3)*-6(m-5)=2m^2-4 | | -16x^2+18x+5=0 | | x=2/3(-6)+1 | | 2x^2+2=4x+5 |